Peran Dinas Lingkungan Hidup dalam Pengendalian Limbah Sabut Kelapa: Sebuah Analisis Hukum dan Administratif di Kabupaten Kotawaringin Timur - Muhamad Hobiri; Jefry Tarantang; Novita Anggraeni (Jurnal Hukum Lex Generalis, 2026)
East Kotawaringin Regency generates 2.024,519 tons of coconut husk waste annually, primarily managed through open burning and water disposal. This study evaluates the effectiveness of the Environmental Department’s (DLH) role in waste control using a normative-empirical approach. Results show that despite Regent Regulation No. 29 of 2022, DLH’s performance remains ineffective. Key barriers include limited institutional capacity, non-integrated budgets, weak coordination, and vast geographical challenges. Enhanced regional policies are essential to optimize waste governance and achieve good environmental governance.